The entry of Theileria parva merozoites into bovine erythrocytes occurs by a process similar to sporozoite invasion of lymphocytes - Shaw, M.K.; Tilney, L.G. (Cambridge University Press, 1995)
The entry of Theileria parva merozoites into bovine erythrocytes in vivo is described and compared to sporozoite invasion of lymphocytes. Merozoites make initial contact with erythrocytes with any part of their surface and invasion of the host cell does not require the reorientation of the apical end of the merozoite towards the surface of the erythrocyte. After the initial attachment the merozoite and host cell membranes form a continual close junction with the 2 apposed membranes separated by a 6-8 nm gap containing moderately dense material. The progressive circumferential 'zippering' of these closely apposed membranes leads to the movement of the parasite into the erythrocyte. The newly internalized merozoite which is completely surrounded by the erythrocyte plasma membrane escapes from this enclosing membrane by a process involving the discharge of at least the rhoptries; whether the merozoite also contain other types of secretory organelles (e.g. micronemes, microspheres or dense bodies) remains to be determined. Morphologically, the events involved in merozoite invasion of erythrocytes are almost identical to the process of sporozoite invasion of lymphocytes but differ significantly from the entry process of the invasive stages of other Apicomplexan parasites.